A comparison of mean corpuscular volume (MCV) between thalassemia-carrier and non-thalassemia-carrier pregnant women receiving highly active antiretroviral therapy (HAART) - Yada Thongyou; Fuanglada Tongprasert (Elsevier, 2017)
Objective: HIV-infected treatment with antiretroviral drugs is one of the common causes of macrocytosis. In patients receiving highly active antiretroviral therapy (HAART), the mean corpuscular volume (MCV) can be shifted from microcytic to normocytic or macrocytic after treatment and significantly affected the thalassemia screening. This study aimed to compare MCV between thalassemia-carrier and non-thalassemia-carrier antiretroviral drug-naïve, HIV-infected, pregnant women receiving HAART. The results will support the couples at risk identification in prenatal control of severe thalassemia disease. Materials and methods: A retrospective cohort study was conducted in antiretroviral drug-naïve, HIV-infected, pregnant women who received HAART between January 2008 and December 2015 in Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand. Changes in MCV were compared between the thalassemia and non-thalassemia carriers. Results: Of 74 pregnant women who were exposed to HAART for at least 4 weeks, increased MCV levels were significantly greater in the non-thalassemia carriers group (n = 58) than in the thalassemia-carrier group (n = 16) (16.60 ± 12.55 fL and 15.61 ± 9.67 fL, respectively; p < 0.001). Pre-HAART exposure, sensitivity of MCV was 83.3% for thalassemia carriers screening using MCV <80 fL. Post-HAART exposure, sensitivity of MCV was 33.3%, and the false negative rate was 66.7%. Conclusion: Post-HAART exposure, MCV increased substantially in both the thalassemia and non-thalassemia carriers. Using MCV <80 fL as the cutoff for diagnosing thalassemia, false negative results were observed in two thirds of the thalassemia carriers who were exposed to HAART for at least 4 weeks; therefore, the screening test should be interpreted with caution.